The Role of Academics in Corporate Social Responsibility to Increase Business Capacity of Micro Small and Medium Enterprises - Tresna Puja Asmara, Teguh; Murwadji, Tarsisius (Jurnal Hukum Positum, 2019)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia has a significant role in national economic development. In addition to supporting the economic growth and providing job opportunities, MSMEs also takes a role in distributing development results. Based on Statistics Indonesia (BPS) in 2016, from a total of 59,693,791 business units in Indonesia, 99.89 percent is MSMEs and its contribution to Indonesia’s Gross Domestic Product (GDP) reached 62.5 percent, workforce absorption up to 95 percent and its contribution to exports non-oil and gas up to 16.45 percent. However nowadays, MSMEs has to face some problems. One of which is related to capital and business development. The capital and business development issues can be solved through Corporate Social Responsibility (CSR) program. Yet, CSR requires a suitable strategy for a successfull and effective implementation. This research is analytical descriptive using normative juridical approach. The results showed that the implementation of CSR could not be felt optimally in order to develop MSMEs. The concept of CSR implementation by the collaboration of stakeholders is expected to provide a solution so that CSR can be implemented appropriately and effectively. One of the stakeholders in CSR is the academics, where CSR in a broad sense can also be a Community Service Program in Universities.